2020
DOI: 10.3390/jcm9103290
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Hospital Lactatemia Predicts 30-Day Mortality in Patients with Septic Shock—Preliminary Results from the LAPHSUS Study

Abstract: Background: Assessment of disease severity in patients with septic shock (SS) is crucial in determining optimal level of care. In both pre- and in-hospital settings, the clinical picture alone is not sufficient for assessing disease severity and outcomes. Because blood lactate level is included in the clinical criteria of SS it should be considered to improve the assessment of its severity. This study aims to investigate the relationship between pre-hospital blood lactate level and 30-day mortality in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Also, most of them provided data on the association between nonsepsis, sepsis, severe sepsis and septic shock and different blood lactate values. Meanwhile, there were 82 studies that demonstrated the relationship between blood lactate and sepsis induced mortality [9,11,15,19,31,34,36,[38][39][40][42][43][44][45][46][47][48][49][50][51]53,55,58,59,62,63,65,[67][68][69][70][71][72][74][75][76]78,81,83,85,[87][88][89]91,93,95,. Additionally, there were 46 articles reported the diagnostic accuracy of blood lactate levels in determining sepsis and associated clinical prognosis [11,15,31,33,34,38,43-45,50,53,56,59,64-67,69...…”
Section: Resultsmentioning
confidence: 99%
“…Also, most of them provided data on the association between nonsepsis, sepsis, severe sepsis and septic shock and different blood lactate values. Meanwhile, there were 82 studies that demonstrated the relationship between blood lactate and sepsis induced mortality [9,11,15,19,31,34,36,[38][39][40][42][43][44][45][46][47][48][49][50][51]53,55,58,59,62,63,65,[67][68][69][70][71][72][74][75][76]78,81,83,85,[87][88][89]91,93,95,. Additionally, there were 46 articles reported the diagnostic accuracy of blood lactate levels in determining sepsis and associated clinical prognosis [11,15,31,33,34,38,43-45,50,53,56,59,64-67,69...…”
Section: Resultsmentioning
confidence: 99%
“…A direct comparison of our findings with other studies is problematic. Lactate and BE are routinely measured in critically ill patients suffering from various diseases, and both serve as mortality predictors in ICU (for example, in post-cardiac surgery patients or those with cardiogenic shock, ruptured abdominal aortic aneurysms, or trauma) [ 4 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Whether BE or lactate concentrations serve as better predictors of mortality in critical care patients has not yet been determined [ 4 , 33 , 34 , 35 , 36 ], with no studies reporting with certainty whether these predictors are both independent and/or additive.…”
Section: Discussionmentioning
confidence: 99%